Efektivitas Penerapan Peraturan Daerah Kabupaten Tanjung Jabung Timur Nomor 5 Tahun 2020 tentang Kawasan Tanpa Asap Rokok di Pusat Kesehatan Masyarakat Simpang Pandan Kecamatan Geragai - Nuraini, Nuraini; Marcellina, Annisa (Universitas Batanghari Jambi, 2024)
This study aims to evaluate the effectiveness of the implementation of Tanjung Jabung Timur Regency Regional Regulation Number 5 of 2020 concerning Non-Smoking Areas at the Simpang Pandan Community Health Center, Geragai District. This study uses an empirical-juridical method with a socio-legal research approach. Data were collected through interviews, documentation studies, and observations of samples selected using a purposive sampling technique. The results showed that the implementation of the Non-Smoking Area Regional Regulation at the Simpang Pandan Community Health Center had been carried out, but was not yet optimal. The effectiveness of implementing the Regional Regulation is still relatively low due to a lack of public awareness, smoking habits, lack of law enforcement, and limited resources. Supporting factors for implementing the Regional Regulation are the commitment of the leadership and staff of the health center, as well as support from the local government. To improve the effectiveness of implementing the Regional Regulation, efforts need to be made such as increasing socialization and education to the public, increasing supervision and law enforcement, and increasing the availability of supporting facilities.